Educação indígena: um estudo sobre a educação formal na aldeia indígena Wajãpi-Aramirã no município de Pedra Branca do Amaparí/AP - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2012)
This study aimed to verify the educational process Aramirã Indian village belonging to the group that is Wajãpi and is located in the municipality of Pedra Branca do Amapari. For both search was made of material support agencies that take care of the Indian as the National Indian Foundation and the State Department of Education. Was used as the basis for the search parameters National Indigenous Schools and the National Benchmark for Indigenous Schools. It was also done field research questionnaires with open questions directed to teachers of the village in order to answer the questions sometimes posed as goals to be achieved. The use of photographs was made to help illustrate this process of formation had in the village. Thus we come to the end of the study showing the importance of this segment of society that despite the difficulties of access to government services is not intimidated and always seek climb improvements to their community.
Keywords: Indígena; Educação formal; Aldeia Wajãpi; CNPQ::CIENCIAS SOCIAIS APLICADAS